Determinasi terhadap Nilai Perusahaan : Studi Emperis Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Syahdina, Aang; Azzahra, Nuraeni; Rizky, Rheza Difa Nur; Wulandari, Elok Setya; Suwandi, Davina Salsabilla; Puspita, Novia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of the Current Ratio (CR), Return on Assets (ROA), and Debt to Equity Ratio (DER) on Company Value in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research uses a quantitative approach with secondary data obtained from 27 out of 46 banking companies selected through purposive sampling. Data analysis was conducted using panel data regression with Eviews 10, supported by several classical assumption tests including normality, multicollinearity, and heteroscedasticity tests. Further analyses include multiple linear regression, t-tests, F-tests, and the Adjusted R² to evaluate the overall model fit. The partial test results show that the Current Ratio has a significant positive effect on Company Value, indicating that higher liquidity strengthens market perception of firm performance. Meanwhile, Return on Assets does not show a significant effect, suggesting that profitability alone is not a determining factor for firm valuation in the banking sector during the observed period. The Debt to Equity Ratio demonstrates a significant positive effect, implying that investors consider leverage an important indicator in assessing banking performance. Simultaneously, all three variables significantly influence Company Value. These findings highlight the importance of liquidity and leverage in shaping investor appraisal of banking companies in Indonesia.